Religious Moderation in Tunjuk Ajar Melayu and Its Integration into the Madrasah Curriculum in Riau - Wan Muhammad Fariq; Munzir Hitami; Zaitun Zaitun (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the values of religious moderation embedded in Tunjuk Ajar Melayu by Tenas Effendy and examines their potential integration into the madrasah curriculum in Riau. Religious moderation is a central educational and sociopolitical concern in Indonesia, particularly in multicultural regions such as Riau, where local wisdom can support national values of tolerance and pluralism. Using a qualitative approach, this research applies Jorge J. E. Gracia’s hermeneutic framework to analyze cultural texts within Tunjuk Ajar Melayu. The study combines literature review and qualitative document analysis based on Altheide’s six-stage model. To enhance validity, data triangulation was conducted through in-depth interviews with cultural experts and individuals closely associated with Tenas Effendy. The findings reveal eleven core values of religious moderation reflected in Malay expressions, poetry (pantun), and moral teachings: Tawassuṭ (moderation), I’tidāl (justice), Tasāmuḥ (tolerance), Shūra (consultation), Iṣlāh (reform), Qudwah (exemplary conduct), Tawāzun (balance), Musāwah (equality), Aulawiyah (prioritization), Taṭawwur wa Ibtikār (innovation), and Taḥaḍur/Ta’addub (civility). These values align with Islamic principles and the goals of Indonesia’s Merdeka curriculum, particularly through the local content subject Budaya Melayu Riau (BMR). The study concludes that integrating Tunjuk Ajar Melayu into religious education can reinforce moderate Islamic character and support culturally grounded curriculum development in madrasahs across Riau.